Tissue cryopreservation using the 3M™ Novec™ 7000 freezing coolant offers a comparable and safe alternative to customary coolants. (3rd April 2022) - Nunez, Victor; Cook, Ashley; Havnar, Charles; Flanagan, Sean; Ge, Nianfeng; Martzall, Angela; Taylor, Robin E.; Lu, Millicent; Mayba, Oleg; Foreman, Oded
ABSTRACT: Cryopreserving tissues for histology requires the use of coolants to buffer the sample from liquid nitrogen (LN2 ) and to control the rate of temperature decline. Several coolants sharing similar physical characteristics are available on the market; however, commonly used coolants are variably flammable and/or toxic and pose risks to personnel and facilities. The purpose of this study was to compare the performance of three commercially available coolants: hexane, 2-methylbutane (2 M), and 1-methoxyheptafluoropropane (N7000). Fresh mouse tissues were frozen by each method, for their ability to preserve microscopic architecture and to protect RNA from degradation were evaluated and compared to tissue characteristics obtained by direct immersion in LN2 . Our results show that for most tissues, the N7000 freezing coolant provides equal or improved preservation of microscopic architecture. While snap-freezing tissues in LN2 provides superior RNA protection, no significant differences in RNA quality were seen between tissues frozen in hexane, 2 M, and N7000.